2006
DOI: 10.1523/jneurosci.0649-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Localization of the Translational Repressor Pumilio 2 and Its Contribution to Dendritic Stress Granules

Abstract: Pumilio (Pum) protein acts as a translational inhibitor in several organisms including yeast, Drosophila, Xenopus, and mammals. Two Pumilio genes, Pum1 and Pum2, have been identified in mammals, but their function in neurons has not been identified. In this study, we found that Pum2 mRNA is expressed during neuronal development and that the protein is found in discrete particles in both the cell body and the dendritic compartment of fully polarized neurons. This finding indicates that Pum2 is a novel candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
181
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(184 citation statements)
references
References 54 publications
3
181
0
Order By: Relevance
“…Because microRNAs exert their effects on mRNAs in processing bodies (P-bodies) or RNA-induced silencing complexes (RISCs) (Anderson and Kedersha, 2006;Parker and Sheth, 2007), this finding suggested that RISC and specifically P-bodies might be involved in this process. We have detected P-bodies in neurons, both in the cell body and in dendrites (Vessey et al, 2006). Furthermore, a recent study reported that P-body (DCP1a, Rck/p54/ DDX6) and transport RNP [FMRP (fragile X mental retardation protein), Staufen (Stau)] markers colocalize in dendrites of Drosophila olfactory neurons (Barbee et al, 2006), raising the possi-bility that P-body components contribute to the translational silencing and/or turnover of dendritically localized mRNAs.…”
Section: Introductionmentioning
confidence: 79%
“…Because microRNAs exert their effects on mRNAs in processing bodies (P-bodies) or RNA-induced silencing complexes (RISCs) (Anderson and Kedersha, 2006;Parker and Sheth, 2007), this finding suggested that RISC and specifically P-bodies might be involved in this process. We have detected P-bodies in neurons, both in the cell body and in dendrites (Vessey et al, 2006). Furthermore, a recent study reported that P-body (DCP1a, Rck/p54/ DDX6) and transport RNP [FMRP (fragile X mental retardation protein), Staufen (Stau)] markers colocalize in dendrites of Drosophila olfactory neurons (Barbee et al, 2006), raising the possi-bility that P-body components contribute to the translational silencing and/or turnover of dendritically localized mRNAs.…”
Section: Introductionmentioning
confidence: 79%
“…We tested this hypothesis using shRNA to down-regulate and a Pum2-EYFP fusion protein to overexpress Pum2, respectively. The efficiency of shRNA-mediated Pum2 (shPum2) down-regulation in dissociated hippocampal neurons has been previously demonstrated (7,12). Hippocampal neurons were transiently transfected at 7 days in vitro (DIV), fixed 3 days later, and subjected to Sholl analysis (13).…”
Section: Resultsmentioning
confidence: 99%
“…For details of all constructs, cloning, and antibodies, see SI Methods. Rat hippocampal neurons were cultured and transiently transfected as described (7,24,25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of PUM2 being involved in this capacity is not unlikely. It will be interesting to determine whether PUM2 binds to the AChE mRNA in CNS neurons because PUM2 is expressed by neurons and is involved in the formation of stress granules in dendrites (17,22). AChE is highly expressed in cholinergic neurons and their targets in the CNS and specifically in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%